L‐Aspartic Acid with Dual Functions: An Eco‐Friendly and Affordable Choice to Accelerate High Salinity Brine Utilization - Suning Mao; Zhen Yu; Jie Chen; Yizhe Shen; Minjie Li; Chen Sun; Xiaoqing Lin; Bin Yang; Tong Chen; Qunxing Huang; Xiaodong Li; Jianhua Yan (Advanced Science)
Abstract L‐Aspartic acid (L‐Asp) poses a dual function, which can affect the evaporation and crystallization process of the high‐salinity brine by altering the physical or chemical properties of the salts. MSWI (municipal solid waste incineration) fly ash washing leachate, as a typical high‐salinity brine, is utilized here to validate this hypothesis under the simulation guidance. Since L‐Asp has stronger adsorption energy on the (110) crystal face of CaCO3, L‐Asp can facilitate the preferential growth of more valuable vaterite during the softening process (pretreatment before crystallization). Subsequently, the resulting solution undergoes a stable interfacial solar‐driven crystallization process under the L‐Asp, with a high salt recovery ratio of 0.14 kg m−2 h−1 within 40 h under 1 sun. Finally, to harness the “cradle to grave” full life cycle utilization of washing leachate, the extracted mixed salts are utilized for moisture‐enabled electricity generation. L‐Asp can significantly enhance this process by reducing the critical relative humidity of mixed salts, thereby exhibiting a stable open circuit potential and short‐cut current of ≈ 0.51 V and 10.6 µA within continuous 800 min. In conclusion, this work not only provides innovative approaches for upcycling high‐salinity wastewater but also explores novel applications for L‐Asp.